Nicotinamide Riboside for Ataxia Telangiectasia: A Report of an Early Treated Individual - Steinbrücker, Katja; Tiefenthaler, Elke; Schernthaner, Eva-Maria; Jungwirth, Julia; Wortmann, Saskia B. (Neuropediatrics, 2023)
A first study on nicotinamide riboside treatment of 24 individuals with ataxia telangiectasia with a mean age of 17.5 years showed improved ataxia scores and immunoglobulin levels. We here present the effect of nicotinamide riboside in another individual with ataxia and recurrent infections in whom treatment started as early as at the age of 3 years and 6 months.During 11 months of follow-up, mean total Scale-for-the-Assessment-and-Rating-of-Ataxia decreased from 27 to 9 points and mean total Score for the Gross-Motor-Function-Measure increased from 61 to 78%. Improvement in drawing skills was observed by ICF-based ergotherapeutic examination. Use of antibiotics and frequency of hospitalizations due to infections were reduced by more than 90%. Immunological parameters in blood remained unchanged. No adverse effects occurred.While the effects on motor and speech improvement might be partly explained by development, our study replicates the previous finding of a positive effect of nicotinamide riboside treatment in ataxia telangiectasia. One could even hypothesize that the early treatment will lead to even better outcome. Given the absence of adverse effects, we strongly encourage to consider nicotinamide riboside in all individuals with ataxia telangiectasia.
Keywords: treatment; exome sequencing; movement disorder; cerebellar syndrome; Louis Bar syndrome